PERLINDUNGAN HUKUM BAGI KORBAN “BANK GELAP” - Hibnu Nugroho Nugroho (Faculty of Law, Universitas Jenderal Soedirman, 2009)
In explanation from Article 18 Constitution Number 18 Year 1998 concerning Banking, it mention that any fund retrieving from society by anyone is an action that need be monitories, this need to done because a lot of funds from the society has been retrieved by those fund retriever. In few last years, we often see may funds retrieving from society that end up with many victims. Mostly, the victims suffer lost of materials. Penalty that gave to the criminal become not important because law in Indonesia that rule about restitution could not be applied maximally. That only wish from the victims are that they will get their money back, but for law enforcer, that the firs action need to be done is to prevent the criminal from escaping., hiding the evidence and prevent anymore victims. Those two opposed interest should not be happen because one purpose of penalty is to keep the balance in society from losing. Kata Kunci : Bank gelap, korban, ganti rugi